Refining waste and elevating customer service: assessing the efficacy of reverse logistics strategies for product returns management - Li, Xiaoyao; Jiang, Bing; Meng, Xueying; Bai, Yang (Journal of combinatorial optimization, 2025)
To enhance the utilization rate of remanufactured products and further facilitate their widespread circulation, it is crucial to identify the responsible party for processing and refurbishing these items. This paper explores the potential contributions of various entities within a supply chain, including new product manufacturers, retailers, and third-party entities, in providing services for recycling and refurbishing remanufactured products. That is to say. It explores the question of which side of the production process of refurbished products can be done in a more economically and environmentally efficient way. The aim is to promote the rational use of resources and address the necessity to enhance the resilience of green supply chains. In this supply chain, remanufactured and new products are introduced to the market simultaneously. This research has developed three competitive cooperation models based on different recycling and refurbishment subjects for refurbished products by considering the return policy, the cost of new and remanufactured products, and the interaction between product prices. These include a model of competition between a separate manufacturer of new products and a separate manufacturer of refurbished products (Model A), a basic model in which a manufacturer of new products also carries on the business of refurbished products (Model B), and a model of competition and cooperation between a manufacturer of new products and a retailer that carries on the business of refurbished products (Model C). Based on a game theory framework, this study analyses in-depth the preference differences among members for different supply relationships of refurbished products in three supply chain models. In this model, owing to diverse return policies, refurbishment costs, and other factors, different members will undertake refurbishing products to maximize the interests of all parties involved. The findings of this paper indicate that the supplier favors Model B when the return policy (r) is small. However, for larger r values, the supplier will opt for either Model A or Model C. Additionally, this paper finds that retailers are more likely to choose Model C when the return policy reaches a specific value. Theoretically, this study extends the existing literature on the value of return policy and fills the gap in research on the impact of return policy on expanding green supply chains. Through developing a new game model, the impact mechanism of return policy in the competition between remanufactured and new products is analyzed in depth, providing academics with a fresh perspective on how to reshape supply chain structures to increase members' profitability. The study provides market management professionals and business managers with valuable insights for strategic decision-making, especially determining which party is responsible for recycling and refurbishing remanufactured products. In addition, the findings provide an important reference for government intervention to effectively expand the market for remanufactured products by adjusting the gap between product return policies, thereby optimizing resource utilization, promoting environmental protection, and enhancing the resilience and sustainability of green supply chains.